Penerapan Baitul Arqam untuk Peningkatan Nilai Al Islam dan Kemuhammadiyah bagi Dosen Universitas Muhammadiyah Mataram - Ilham Ilham; Arsyad Abdul Gani; Rudi Arrahman (Universitas Muhammadiyah Surabaya, 2019)
Baitul Arqam for lecturers is the principal regeneration training held to unify the vision and build understanding of ideological values, systems, and real movement for lecturers within the Muhammadiyah Universities. The Baitul Arqam training for lecturers of the Muhammadiyah University of Mataram is to build an understanding ideology of Muhammadiyah, strengthening self-identity as a Muhammadiyah community, increasing commitment and integrity in developing Muhammadiyah's charities and organizations, and to build an excellent and Islamic teaching staff of Muhammadiyah University of Mataram. Participants of Baitul Arqam are 32 lecturers. The methods used in this training are varied lectures, demonstrations, simulations, and discussions. For assessment the participants was using the Context, Input, Process and Product (CIPP) model based on cognitive, affective, and psychomotor aspects. Based on the analysis results, the average score of participants in the cognitive aspect was 75.7, affective 76.5 and psychomotor 74.13. Thus, the level of understanding of contract lecturers at Muhammadiyah University of Mataram was good. So, the applied of Baitul Arqam has effect in increasing the participants’ understanding towards Al Islam and Kemuhammadiyahan values for the lectures of Muhammadiyah University of Mataram.